Kajian Geometri Peledakan untuk Mendapatkan Fragmentasi Yang Optimal Pada Penambangan Batu Andesit PT. Atika Tunggal Mandiri Kabupaten 50 Kota Provinsi Sumatera Barat - Yuri Purwa Agung Hs; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. Andesite Mining at PT. Atika Tunggal Mandiri with a surface mining system with the Quarry mining method. The percentage of boulder-sized blasting fragmentation produced at this time in the field is 38.19%. As a result, the diggability of the digging tool is not optimal and the excavation tool productivity target planned by the company is 80 bcm / hour not achieved. This study aims to design a new blasting geometry to obtain optimal fragmentation results so that loading activities are effective and productivity targets are achieved. The research method was carried out by providing recommendations for blasting geometries based on R.L. Ash and C.J. Konya and carried out the application of one of the blasting geometry designs in the field so that the optimum blasting geometry design was obtained from one of the blasting geometry designs to be applied in the future for the company. The basis of the results of the application in the field to one of the proposed blasting geometry designs, namely: Burden: 2 m, spacing: 2 m, Stemming: 1.4 m, Subdrilling: 0.6 m, level height: 3 m, blast hole depth 3.5 m, powder coloum: 1.5 m, and powder factor: 0.68 kg / m3 where the fragmentation of the boulder size resulting from the split desktop software analysis is 0% and digging time is 9.61 seconds.Keywords : Blasting Geometry, Blasting Fragmentation, Digging Time, Bucket Fill Factor